PENDAFTARAN TANAH SISTEMATIS LENGKAP DI DESA BAWURAN, KECAMATAN PLERET, KABUPATEN BANTUL, YOGYAKARTA - Naufal Tsaqif Wahidhadi; Listyowati Sumanto (Fakultas Hukum Universitas Trisakti, 2021)
Complete Systematic Land Registration is a land registration activity for the first time that is carried out simultaneously for all land registration objects in one village/kelurahan area, which includes the collection of physical data and juridical data regarding one or several land registration objects for the purpose of registration. The formulation of the problem is whether land registration through the Complete Systematic Land Registration program in Bawuran Village, Pleret District, Bantul Regency, Special Region of Yogyakarta complies with the provisions of the Minister of Agrarian Affairs and Spatial Planning Number 6 of 2018 concerning Complete Systematic Land Registration. The research uses normative juridical research type, is descriptive in nature, and uses primary and secondary data, the results of the research are analyzed qualitatively and conclusions are drawn using a deductive mindset. In conclusion, the implementation of the Complete Systematic Land Registration Program in Bawuran Village, Pleret District, Bantul Regency has been carried out in accordance with the provisions of the Minister of Agrarian Affairs and Spatial Planning Number 6 of 2018 concerning Complete Systematic Land Registration.